2020
DOI: 10.1002/app.49851
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of polypropylene by cellulose microfibers modified with polydopamine and octadecylamine

Abstract: Cellulose microfibers (CMFs) having surfaces modified with polydopamine (PDPA) and octadecylamine (ODA) were prepared, and their reinforcing abilities for polypropylene (PP) were investigated. The PDPA coating was made via self‐polymerization of dopamine (P‐CMF), and subsequent alkylation was conducted by the reaction with ODA (OP‐CMF). The modified CMFs exhibited improved dispersibility in the PP matrix due to the reduced hydrophilicity. The OP‐CMF/PP composite prepared by batch mixing had a higher tensile mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The composites' damping peak suggested that once a material has been deformed, it would not return to its previous shape. With the addition of esterified CNC, the peak amplitude increased by 1.7°C at high temperature, indicating a higher degree of molecular mobility 34 . The esterified CNC in the composites may have improved its interaction with the PP matrix, which could have been the explanation.…”
Section: Resultsmentioning
confidence: 94%
“…The composites' damping peak suggested that once a material has been deformed, it would not return to its previous shape. With the addition of esterified CNC, the peak amplitude increased by 1.7°C at high temperature, indicating a higher degree of molecular mobility 34 . The esterified CNC in the composites may have improved its interaction with the PP matrix, which could have been the explanation.…”
Section: Resultsmentioning
confidence: 94%
“…Unexpectedly, with the increase of ODA concentration, the excessive coating may reduce the roughness of the surface of fiber, thus inhibiting the entanglement between fiber and the polypropylene molecular chains. In addition, excessive ODA could be regarded as an “interface lubricant,” which made the tensile strength and tensile modulus of the composites tend to decrease, and the elongation at break gradually increase 38 …”
Section: Resultsmentioning
confidence: 99%
“…The P-RF was further modified by introducing octadecyl chains via Michael addition of the catechol group with the amino group of ODA. 38 In addition, during PDA formation, DA (covering on fiber) could be oxidized into chinone, providing the carbonyl groups for reacting with NH 2 on ODA by the Schiff base reaction. 39 ODA was dissolved in ethanol to a concentration of 0.5/1/2/4/8 g/L.…”
Section: Rf Surface Modificationmentioning
confidence: 99%
“…Clearly, there is a compromise of the recovery between low-ring and high-ring PAHs. [51][52][53] Considering the recoveries of all 16 PAHs within an acceptable range, 0.25 mg mL −1 ODA was selected for further optimization. Next, we investigated the effect of reaction time on the recoveries of PAHs as the time was varied from 0.5 h to 4 h. As shown in Fig.…”
Section: Modication Of Pda Coatingmentioning
confidence: 99%